Legal Perspective and Public Values in Family Planning Services: Analysis at the Jambi City Population Control and Family Planning Service - Fadilah Salsabila Armand (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Based on the problems that occur in the city of Jambi, the unmet need rate is still high and does not reach the target this indicates a lack or absence of public value in providing family planning services. This study aims to describe, analyze and explain public value in family planning services at the Jambi City Population Control and Family Planning Office. This research uses a descriptive qualitative method with a case study approach. The results showed that DPPKB Jambi City did not fulfill one dimension of Public Value in providing Family Planning (KB) services to the community, in other words, it had not created optimal public value in providing KB services in the substantial value dimension.     Keywords:Public Service; Public Value; Family Planning;